1995
DOI: 10.1073/pnas.92.26.12195
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of a single chlorophyll is correlated with the photoinhibition of photosystem II with a transiently inactive donor side.

Abstract: Pigments destroyed during photoinhibition of water-splitting photosystem II core complexes from the green alga Chiamydomonas reinhardtii were studied. Under conditions of a transiently inactivated donor side, illumination leads to an irreversible inhibition of the electron transfer at the donor side that is paralleled by the destruction of chlorophylls a absorbing maximally around 674 and 682 nm. The observed stochiometry of 1 + 0.1 destroyed chlorophyll per inhibited photosystem II suggests that chlorophyll d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 58 publications
(103 reference statements)
1
16
0
Order By: Relevance
“…3a, insert) is consistent with the hypothesis that under UVBR stress conditions, there is an active down regulation of photosynthesis in the cells for achieving protection (Malanga et al, 1997). PSII is one of the main targets likely to be affected by UVR (Melis et al, 1992), and several sites might be susceptible to damage (Bumann & Oesterhelt, 1995) in association to the D1 protein, which connects the primary electron donors with the active PSII receptors. Leu et al (2006) reported a decrease in optimum quantum yield of PSII between day 6 and 15 in the Arctic diatom Thalassiosira antarctica var.…”
Section: Discussionsupporting
confidence: 69%
“…3a, insert) is consistent with the hypothesis that under UVBR stress conditions, there is an active down regulation of photosynthesis in the cells for achieving protection (Malanga et al, 1997). PSII is one of the main targets likely to be affected by UVR (Melis et al, 1992), and several sites might be susceptible to damage (Bumann & Oesterhelt, 1995) in association to the D1 protein, which connects the primary electron donors with the active PSII receptors. Leu et al (2006) reported a decrease in optimum quantum yield of PSII between day 6 and 15 in the Arctic diatom Thalassiosira antarctica var.…”
Section: Discussionsupporting
confidence: 69%
“…Allomerization of Chl a occurs when the enolate anion of Chl a is oxidized by free radicals (Hynninen 1991). In vitro, it is inhibited by the presence of ␤-carotene (Hynninen 1991), which is believed to primarily scavenge 1 O 2 (Bumann and Oesterhelt 1995). Although alternative models for allomerization have been presented, it is thought to be principally driven by 1 O 2 as opposed to other reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…When PSII core complexes were illuminated in the absence of Ca 2+ and Cl − , a chlorophyll molecule was oxidized simultaneously with the inhibition of CaCl 2 -dependent oxygen evolution [93]. The ChlD1 and ChlD2 molecules have the chlorine ring almost parallel with the membrane plane [94] like the chlorophyll first oxidized in donor-side photoinhibition [93], but stable oxidation of these chlorophylls is unlikely because both are part of P 680 + . The EPR signal related to oxidized tyrosine D (a tyrosyl residue of D2 protein) is lost later [84,88], and finally the capacity for primary charge separation and reduction of Q A disappear [83,84].…”
Section: Preparations With Inhibited Donor Sidementioning
confidence: 99%